Needs Analysis of English for Specific Purposes on Islamic Boarding School Students - Helmi Abdul Latif (Universitas Hamzanwadi, 2019)
This study aims to analyze the needs of students in learning English for special purposes (ESP) with the theme of Islamic boarding schools. The researcher used questionnaire and interview to obtain data. The results show that there are differences in the English learning needs of students in Islamic boarding schools and students who are not in Islamic boarding schools. The subjects in pesantren can be used as English learning material for special purposes such as fiqh, history, ahlaq, da'wah, etc. In addition, learning English at Islamic boarding school-based institutions makes students get used to practice using English for daily activities.